New Psychoactive Substances Pharmacology, Clinical, Forensic and Analytical Toxicology (Handbook of Experimental Pharmacology,, 2018)
This volume is designed to feature the pharmacology of new psychoactive substances, legislative aspects, information exchange including epidemiology, and clinical, forensic, and analytical toxicology in order to facilitate the understanding of this complex and rapidly developing phenomenon.